Полісся в давньоукраїнських літописах - Мишанич, Я.О. (Археологія і давня історія України, 2016)
У статті йдеться про літописну інтерпретацію історії Полісся. З цією метою автор звернувся до літописної трилогії — «Повісті временних літ», Київського та Галицько-Волинського літописів. Автор рассказывает о древней истории Полесского края в составе средневековой Украины. Речь идет о
легендах и летописных рассказах, о старокиевских князьях Олеге Вещем, Игоре, Святославе Храбром,
княгине Ольге, Ярославе Мудром и др. Также автор говорит о средневековых славянских поселениях в
диких лесах, на берегах рек и болот. Автор использовал три летописи, известных нам как «Повесть временных лет», Киевская летопись и Галицко-Волынская летопись. В них рассказывается много интересного о
древних полесских городах, таких как Искоростень, Овруч, Мичск, Чернобыль, Туров, Любеч, Дубровица,
Городен, Небль, Камень, Глухов, Новгород-Северский, Стародуб, а также о людях, которые жили на
этой земле и сражались за нее, когда приходило время. Речь идет также об основателе Киево-Печерского монастыря Антонии — уроженце Любеча, который после паломничества в Грецию решил вернуться и основать монастырь неподалеку от Киева над рекой Днепр. The paper deals with ancient history of Polissyan region
in medieval Ukraine. There are many legends and
romantic tales about Old Kyivan princes, such as Oleh
the Prophetic, Ihor, Sviatoslav the Brave, Olha, Yaroslav
the Wise etc. A lot of interesting legends about medieval
settlements in wild forests, near rivers and
swamps survived. The author has analysed three medieval
chronicles, known as the «Tale of Bygone Years»
(Povist’ vremennyh lit), Kyivan Chronicle (Kyivskyy litopys)
and Chronicle of Halychyna and Volhynia («Halytsko-
Volynskyy litopys»). They told us about such
Polissyan towns like Iskorosten, Ovruch, Mychsk, Chornobyl,
Turiv, Lyubech, Dubrovytsia, Goroden, Neble, Kamin, Glukhiv, Novgorod-Siversky and Starodub;
people who lived, worked there and struggled with enemies when it was necessary. It comes about the Pechersk
Monastery founder, named Antony born in Lyubech, who travelled to Greece, later came back to Kyiv
and founded well-known Monastery in the Caves at the bank of the Dnieper river.